CORELLATION OF STRESS LEVEL DURING COVID-19 PANDEMIC AND THE INSIDENCE OF ACNE ON STUDENTS: STUDY ON UNDERGRADUATE STUDENTS OF THE FACULTY OF MEDICINE OF DIPONEGORO UNIVERSITY - Fanti Saktini (Diponegoro International Medical Journal, 2022)
Background: Acne vulgaris (Acne) is the most common inflammatory disease of skin among adolescents and young adults (85%). Corona Virus Disease (COVID-19) pandemic had enforced lockdowns and thus inevitably converted the conventional schooling system to online learning. These changes raised psychological burden among students, including medical students. Psychological distress might influence the emergence of acne or added its severity.Aim: To know the correlation between stress level during pandemic and the incidence of acne vulgaris among students in Faculty of Medicine Diponegoro University.Method: This study used cross-sectional design, incorporating 97 undergraduate students (batch of 2018-2020) of Faculty of Medicine Diponegoro University, whom suffered from acne, had consented to participate consecutively. Data consisted of subjects’ characteristic and Depression and Anxiety Stress Scale 21 questionnaire. These data were analysed using Chi-square test.Results: Most of the subjects suffered from acne (60.8%), whereas the level of stress varied from normal (61.9%), mild (25.8%), moderate (9,3%), to severe (3.1%). There was no significant relationship between stress level during COVID-19 pandemic and the incidence of acne vulgaris among subjects. (p=0,805).Conclusion: There was no significant relationship between stress level during COVID-19 pandemic and the incidence of acne vulgaris among medical students.